2003
DOI: 10.1002/adem.200300397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypervelocity Impact on Microcellular Ceramic Foams from a Preceramic Polymer

Abstract: Orbiting spacecrafts and satellites are exposed to hypervelocity impacts against orbiting objects of various nature (natural, such as meteorites, or deriving from human artifacts, such as molten sodium and potassium metal alloys, aluminum and alumina particles or plastics), traveling at speed of up to 15 km s ±1 . [1] Hence, special protecting measures have to be implemented to reduce the risk of damages to satellites and spacecraft components. Suitable shields have to perform several functions, from the fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 5 publications
3
12
0
Order By: Relevance
“…Porous fillers as part of all-aluminum multi-wall systems were also considered by Colombo et al (2003) and Li et al (2004). In nearly all of the studies, the results showed that the composite material bumpers faired at best only marginally better in terms of ballistic limit of the dual-wall systems than their equivalent monolith aluminum counterparts (see also Robinson and Nolen, 1995;Sil'vestrov et al, 1999a,b;Tamura and Mutou, 2005).…”
Section: Composite Outer Bumpersmentioning
confidence: 96%
“…Porous fillers as part of all-aluminum multi-wall systems were also considered by Colombo et al (2003) and Li et al (2004). In nearly all of the studies, the results showed that the composite material bumpers faired at best only marginally better in terms of ballistic limit of the dual-wall systems than their equivalent monolith aluminum counterparts (see also Robinson and Nolen, 1995;Sil'vestrov et al, 1999a,b;Tamura and Mutou, 2005).…”
Section: Composite Outer Bumpersmentioning
confidence: 96%
“…This is because sintering after foaming reduces the porosity, and inevitably, the sintering process results in the exclusion of some pores. The mechanical properties of ceramics dominated by open pores have been improved, [10][11][12] but they are still inadequate, owing to weak inter-grain bonding in addition to the smaller bulk area.…”
mentioning
confidence: 99%
“…The Si-O-C has a wide range of applications such as structural materials [37], reinforcement materials [38] and catalyst support [39]. Si-O-C has been prepared as bulk [40], foams [37] and fibers [38,41,42]. However, nanotubes comprising Si-O-C has not been reported.…”
Section: Introductionmentioning
confidence: 98%
“…Silicon oxycarbide, a carbon containing silicate, has been synthesized as tetrahedral network of Si-O and Si-C [34,35], carbon-dispersed black glass [34] and porous glass [36]. The Si-O-C has a wide range of applications such as structural materials [37], reinforcement materials [38] and catalyst support [39]. Si-O-C has been prepared as bulk [40], foams [37] and fibers [38,41,42].…”
Section: Introductionmentioning
confidence: 99%